2020
DOI: 10.1177/2050640620901973
|View full text |Cite
|
Sign up to set email alerts
|

Multiple risk factors for diabetes mellitus in patients with chronic pancreatitis: A multicentre study of 1117 cases

Abstract: Background: Diabetes mellitus is a common complication of chronic pancreatitis. It is traditionally considered to develop as a consequence of beta cell loss, but there might be additional factors. Recent studies have highlighted the importance of type 2 diabetes-related risk factors in this context and population-based studies show increased risk of diabetes following acute pancreatitis. The aim of this study was to explore multiple risk factors for diabetes in patients with chronic pancreatitis. Methods: We c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 32 publications
1
23
2
1
Order By: Relevance
“…This type of diabetes is known as type 3c diabetes. Diabetes is more common in patients with pancreatic calcifications, pancreatic exocrine insufficiency and those who underwent surgery[ 23 , 24 ]. In a meta-analysis including fifteen studies (8970 patients), the incidence of DM was 30% and the prevalence increased after 5 years of CP diagnosis[ 26 ].…”
Section: Risk Of Pc In Type 3c Diabetesmentioning
confidence: 99%
“…This type of diabetes is known as type 3c diabetes. Diabetes is more common in patients with pancreatic calcifications, pancreatic exocrine insufficiency and those who underwent surgery[ 23 , 24 ]. In a meta-analysis including fifteen studies (8970 patients), the incidence of DM was 30% and the prevalence increased after 5 years of CP diagnosis[ 26 ].…”
Section: Risk Of Pc In Type 3c Diabetesmentioning
confidence: 99%
“…Other studies have also revealed similar findings: Other risk factors of diabetes, such as the loss of beta-cell mass, also need to be considered. Risk factors also include someone being overweight and having dyslipidemia (Olesen et al, 2020). Increased vagal input related to diet-induced obesity can contribute to extensive innervation by increasing β-cell mass and altering insulin sensitivity (Khemka & Banerjee, 2017).…”
Section: The Relationship Between Body Mass Index and The Occurrence Of Diabetesmentioning
confidence: 99%
“…It is likely that patients with CP will undergo interventional procedures such as pancreatectomy (including Frey’s procedure) for various reasons including intractable pain. Indeed, recent studies have shown that pancreatic surgery is a strong and independent risk factor for the development of diabetes in CP patients[ 55 , 56 ]. It is of great interest to determine the changes in islet cell function following an intervention and how these changes translate into the development of diabetes.…”
Section: Effect Of Different Interventions On Islet Cell Function In mentioning
confidence: 99%